Herbal medicine: a promising approach for the treatment of Alzheimer's disease - Vishnumukkala, Thirupathirao; Gopalakrishna, Prarthana Kalerammana; Jagadeesan, Saravanan; Musa Chiroma, Samaila; Mohd Nor, Nurul Huda; Baharuldin, Mohamad Taufik Hidayat; Thomas, Warren; Mohd Moklas, Mohamad Aris (Mahadev Publications, 2024)
Alzheimer's disease is a progressive neurodegenerative disease manifesting in cognitive decline, impairment of memory, and behavioural deterioration. Alzheimer’s is a relatively common type of dementia. The pathological basis for the progression of Alzheimer's disease is beta-amyloid protein accumulation, phosphorylation of tau protein, abnormal glial cell function, inflammation, neurotransmitter imbalance, along with oxidative stress in brain tissue. Current available therapies are targeted at amelioration of symptoms alone and focus on a limited spectrum of pathophysiological processes. It is evident that it is essential to develop a multi-target therapeutic option in managing Alzheimer's disease, in view of the broad range of factors in disease progression and sever consequences for sufferers. Herbal medicines are seen as a potential resource in the treatment of Alzheimer's disease, in view of their historical use in traditional medicine as neuroprotectants. Herbal medicines have been evaluated in animal studies designed to determine their capacity to prevent neurodegenerative disease and ameliorate memory defects. This review elaborates on the studies conducted on several medicinal plants that have been investigated for their potential in the prevention and treatment of memory defects in animal models.